The Prevalence, Etiological Agents, Clinical Features, Treatment, and Diagnosis of HIV-Associated Oral Candidiasis in Pediatrics Across the World: A Systematic Review and Meta-Analysis - Rafat, Zahra; Sasani, Elahe; Salimi, Yahya; Hajimohammadi, Samaneh; Shenagari, Mohammad; Roostaei, Davoud (Frontiers in Pediatrics, 2021)
In HIV-infected pediatrics, oral candidiasis (OC) is a global issue of concern due to its association with dysphagia, malnutrition, and mortality. The present systematic review and meta-analysis are the first to determine the prevalence of OC in HIV-infected pediatrics worldwide. We searched international (PubMed, Web of Science, Scopus, and Embase) databases for studies published between January 2000 to May 2020 reporting the epidemiologic features of OC in HIV-infected pediatrics. Inclusion and exclusion criteria were defined to select eligible studies. Data were extracted and presented according to PRISMA guidelines. The results of the meta-analysis were visualized as a forest plot. Heterogeneity was also analyzed using the I2, and τ2 statistics. The publication bias was evaluated using Egger test. The literature search revealed 1926 studies, of which 34 studies met the eligibility criteria, consisting of 4474 HIV-infected pediatrics from 12 different countries. The overall prevalence of OC among HIV-infected pediatrics was 23.9 % (95% CI 17.3–32.0 %), and Candida albicans was the most prevalent etiologic agent. Pseudomembranous candidiasis was the predominant clinical manifestation in HIV-infected pediatrics suffering from OC. Thirty articles involving 4051 individuals provided data on HIV treatment status. Among the 4051 individuals, 468 (11.53%) did not receive HIV treatment. The data from 11 articles demonstrated that HIV treatment was significantly associated with a reduction in oral Candida colonization or infection. In contrast, others showed the opposite relationship or did not report any statistical data. A high level of I2 (I2 = 96%, P < 0.01) and τ2 (τ2 = 1.36, P < 0.01) was obtained among studies, which provides evidence of notable heterogeneity between studies. OC is approximately frequent in HIV-positive children. Therefore, efforts should be made to teach dental and non-dental clinicians who care for HIV-infected pediatrics to diagnose and treat this infection.